ENVIRONMENTAL IMPACT OF PUBLIC TRANSPORT IN THE GÓRNOŚLĄSKO-ZAGŁĘBIOWSKA METROPOLIS - Bartosz (Scientific Journal of Silesian University of Technology. Series Transport)
This paper discusses the environmental characteristics of assets of the public transport systems in Górnośląsko-Dąbrowska Metropolis. The public transport is served by a number of companies. This poses the problem of integrating their behaviour in a coherent manner for environment protection. The Metropolis includes regions highly populated with good road networks as well as small localities which generates small transport demands. The transport potential is assessed and categorised in relation to its impact on the environment. The volume of emission of pollutants and the severity of their presence in the environment are summarised. Conditions of the functioning of the constituents of the systems were analysed, accounting for their contribution to pollution as well as health hazards cases.